"Be Creative in Whatever We Do": Minority Culture Creativity on the Uyghur Internet. (27th October 2020) - Meloche, Alysha; Clothey, Rebecca
Abstract: Creativity is often explored from a Western‐dominant perspective. This means that cultures that do not follow dominant culture or Western principles, such as non‐Western or minority ethnic cultures, are often misjudged in creativity research and assessment. Additionally, scholarship that does address Asian creativity does so in a way that presents Asian culture as monolithic. This article presents an example of how creativity is defined, recognized, and enacted in four interactive Uyghur language websites that were active between 2014 and 2016. These Uyghur language websites present an interesting example of how an Asian, ethnolinguistic minority culture expresses creativity and innovation while under controlling and conforming pressures of the dominant culture (in this case the Chinese government). Findings suggest that Uyghurs define their creative identity as one that promotes love, joy, and hope for their community, overcomes adversity, and comes from a heritage of scholars and writers. They recognize creativity that aids in community cultural preservation, is selfless, and is the result of hard work. As a result of their controlled status, online Uyghurs articulate that their creativity is limited by the majority culture and emphatically express how their cultural creativity is unique.